First record of the invasive mosquito species Aedes koreicus (Diptera, Culicidae) in the Republic of Kazakhstan - Andreeva Yulia V.; Khrabrova Natalia V.; Alekseeva Svetlana S.; Abylkassymova Gulnar M.; Simakova Anastasia V.; Sibataev Anuarbek K. (Parasite, 2021)
The natural distribution range of Aedes koreicus is Korea, China, Japan, and the Russian Far East. Since 2008, this species has been recorded as an invasive species in some European countries (Belgium, European Russia, Germany, Hungary, Italy, Slovenia, and Switzerland). The invasive mosquito species Ae. koreicus is reported from the Republic of Kazakhstan for the first time. Its morphological identification was confirmed by molecular-genetic analyses of ND4 sequences using specific primers. Aedes koreicus larvae were found in an artificial water reservoir together with the larvae of Culiseta longiareolata and Culex pipiens s.l. Aedes koreicus successfully overwintered in Almaty at low winter temperatures in 2018–2019. This suggests that the Ae. koreicus acclimation capacity is greater than it has been considered until now. We assume that Ae. koreicus will spread over the west and south of the Republic of Kazakhstan and territories of Kyrgyzstan and Uzbekistan Republics bordering the Almaty region.